The Effect of Single Leg and Double Leg Bounding Exercise Programme (BEP) on Increasing Physical Abilities, Strength, and Agility - Mohammad Zaim Zen; Hari Setijono; Nining Widyah Kusnanik (Britain International for Academic Research (BIAR) Publisher, 2021)
The purpose of this study was to investigate and examine the effect of using the Single Leg and Double Leg Bounding Exercise Program (BEP) on the Improvement of Physical Strength and Agility. The subjects of this study were physical education students class 2017 STKIP PGRI Jombang with 42 people. This type of research is quantitative with a quasi-experimental technique (quasi-experimental). Sampling used the solvin formula and purposive sampling technique. The process of collecting data for the initial and final tests used a leg dynamometer test to determine leg muscle strength and the side-step test for agility. The study results on normality and homogeneity tests showed normal and homogeneous data results with a significance value above 0.05. The mean difference test was carried out using the paired test and the Manova test. The method of increasing the ability of strength and agility has a significant improvement with the two experimental methods.